2018
DOI: 10.3389/fneur.2018.00296
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hand Muscle Structural Modifications in Chronic Stroke

Abstract: The purpose of the study is to assess poststroke muscle structural alterations by examining muscular electrical conductivity and inherent electrophysiological properties. In particular, muscle impedance and compound muscle action potentials (CMAP) were measured from the hypothenar muscle bilaterally using the electrical impedance myography and the electrophysiological techniques, respectively. Significant changes of muscle impedance were observed in the paretic muscle compared with the contralateral side (resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Significantly lower X and θ values were observed in the affected than in unaffected TA muscle. This outcome was in line with the findings of previous studies that θ could be a sensitive biomarker in the measurement of muscle structure and component properties (Li X. et al, 2017; Zong et al, 2018). However, there was no significant difference in the ultrasound parameters between the affected and unaffected sides.…”
Section: Discussionsupporting
confidence: 92%
“…Significantly lower X and θ values were observed in the affected than in unaffected TA muscle. This outcome was in line with the findings of previous studies that θ could be a sensitive biomarker in the measurement of muscle structure and component properties (Li X. et al, 2017; Zong et al, 2018). However, there was no significant difference in the ultrasound parameters between the affected and unaffected sides.…”
Section: Discussionsupporting
confidence: 92%
“…We would therefore anticipate patient/healthy differences in EIM phase angle to manifest at frequencies in which the current crosses the capacitance of the sarcolemma, which was indeed the case. Some recent studies have indicated that EIM may be able to detect muscle changes secondary to UMN dysfunction (Li et al , 2017, Zong et al , 2018. While a mixed UMN/LMN dysarthria is the most common pattern encountered in ALS (Aronson et al , 1992), it remains to be determined if dual pathology can be separated or quantified, either in the tongue or limb muscles.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the alteration of muscle impedance of the biceps brachii (Li et al, 2017) and the hypothenar muscle (Zong et al, 2018) after the occurrence of stroke. These findings supported that reactance (X) and phase angle (θ) were stable and sensitive biomarkers in the assessment of muscle intrinsic properties.…”
Section: Electrical Impedance Myographymentioning
confidence: 99%